Is the green credit policy useful for improving energy intensity? Evidence from cities in China - Ting Pan; Boqiang Lin (Financial Innovation)
Abstract The green credit policy (GCP) is an essential financial policy tool for solving the problem of environmental pollution, and urban energy conservation is an effective way to achieve the goal of carbon neutrality. However, existing research has not verified the energy-saving effects of green credit (GC) at the city level. Based on panel data from 283 cities in China, this study aims to investigate whether GC can effectively reduce urban energy intensity (EI), which is an important complement to existing research. In terms of research methods, to better evaluate the effect of the policy and exclude the influence of other relevant factors, this study considers the promulgation of the Green Credit Guideline (GCG) in 2012 as the basic event, uses the difference-in-differences (DID) model to investigate the impact of GC on EI, and discusses the main impact mechanism. The key results are follows. (1) GC can effectively reduce urban EI. (2) Public environmental demand positively regulates the negative correlation between GC and EI. (3) GC reduces EI through three main channels: government support, capital investment, and technological innovation; however, the mechanism of industrial structure has no significant effect. (4) The effect of GC is more significant in areas with large urban scales, low environmental regulation intensity, and high industrial agglomeration. Based on the above results, this study presents puts forward targeted policy recommendations to strengthen the role of GC in urban sustainable development.